The Use of Woodland Lichen Pasture by Reindeer in Winter with Easy Snow Conditions - Kumpula, Jouko; Lefrère, Stéphanie C.; Nieminen, Mauri (ARCTIC, 2004)
Our aim was to investigate the amount of digging work (cratering) done by semi-domesticated reindeer (Rangifer t. tarandus) in woodland lichen pasture and the effect of snow and pasture conditions on the body condition of female reindeer. From 17 February until 21 April 2001, eight barren reindeer females were allowed to graze freely in a fenced area (20 ha). Measurements before the study showed the amount of lichens within the fenced area to average 632 kg DM/ha in dry pine forest. Inside the fenced area, there was 31.1 cm of relatively soft snow in February and 41.8 cm in April. Observations showed that in February the reindeer spent 39.8% of the time digging and grazing and 1.0% foraging arboreal lichens. In April, they spent 29.8% of the time digging and grazing and 5.2% foraging arboreal lichens. During cratering, reindeer foraged (dug and picked food) with a certain repeated rhythm, using both front feet equally. The size of the grazed area and the volume of snow removed from a single crater were dependent on the total foraging time per crater. The mean body mass of the reindeer was 67.1 ± 2.67 kg in mid-February and 64.9 ± 2.98 kg in late April. It was calculated that in February one reindeer dug and grazed 75.6 m² per day, and the mean change in reindeer body mass was actually +39 g per day. In April the corresponding figures for one reindeer were 60.1 m² and -27 g per day. In the snow and pasture conditions prevailing during this study, the reindeer were able to get enough food and thereby energy to preserve their body condition well. Notre but était de déterminer l'importance du creusage (fouissage) effectué par le renne semi-domestique (Rangifer t. tarandus) dans les pâturages de lichen forestier, ainsi que les répercussions des conditions de la neige et du pâturage sur l'état corporel du renne femelle. Du 17 février au 21 avril 2001, on a laissé huit rennes femelles non gravides brouter à leur guise dans un emplacement clôturé (20 ha). Des mesures effectuées avant le début de l'étude montraient que ...